Malignant pheochromocytoma and paraganglioma: A population level analysis of long‐term survival over two decades12. Issue 6 (11th December 2012) - Goffredo, Paolo; Sosa, Julie A.; Roman, Sanziana A.
Abstract Background and Objectives Pheochromocytoma (PHEO) and paraganglioma (PGL) are rare tumors. Aims of this study were to describe and to compare demographic, clinical, pathologic, and survival characteristics of malignant PHEO and PGL. Methods Patients were identified in SEER, 1988–2009. Analyses included chi‐square, ANOVA, Kaplan–Meier, and Cox proportional hazard regression. Results Gender distribution and mean age were similar for PHEO and PGL. Surgery was performed in 74.3% of PHEO and 78.9% of PGL; external beam radiation was administered in 8.0% of PHEO and 28.1% of PGL (P < 0.001). Compared to PGL, PHEO were larger (mean size 7.7 vs. 4.5 cm PGL, P = 0.001) and more were SEER‐staged as localized (17.3% vs. 49.6%, respectively, P < 0.001). PGLs were more often located in the trunk than in the head/neck (53.8% vs. 38.0%, P < 0.001). PHEO had lower overall and disease‐specific survival than PGL (54.0% and 73.5% vs. 73.3% and 80.5% for PGL, respectively, P < 0.001 and P = 0.118). Independent factors associated with mortality for PHEO included not undergoing surgery and metastases at diagnosis; for PGL, these were age 61–75 years, size ≥5 cm, and presenting with metastases. Conclusions Malignant PHEO has a more aggressive course than malignant PGL; long‐term survival has not improved over the last two decades. Multi‐institutional efforts should be pursued to seek novel treatments. J. Surg. Oncol. 2013;107:659–664. © 2012 Wiley Periodicals, Inc.